Strategies and Initiatives in Acculturation: Voices from Ghana - Boafo-Arthur, Susan; Attah, Dzifa A.; Boafo-Arthur, Ama; Akoensi, Thomas D. (Journal of International Students, 2017)
Culture shock and acculturation are salient aspects of any international study trip. Over the years, many institutions have devised several strategies to help international students transition to life in the host country. However, most of these strategies are insensitive to diverse cultural or country specifics. Drawing from Social Learning Theory, this paper provides narratives from four former students from the West African country of Ghana and how they navigated the process of acculturation in their respective host nations. The narratives discuss their feelings during the study abroad trip, some of the challenges they faced, and personal as well as institutional strategies that aided in ameliorating the experience of culture shock. A few recommendations for Student Affairs Practitioners are also provided.